How should prospective research be designed to legitimately assess the value of urodynamic studies in female urinary incontinence - TARCAN, TUFAN (My University, 2023)
Aims: Since formal evidence demonstrating the value of urodynamic studies (UDS) in functional urology remains elusive, we aimed to consider how best to design robust research for this purpose in female urinary incontinence. Methods: An expert group was convened to debate the following considerations: (a) precedents for formally proving the value of a gold standard diagnostic test, (b) key research principles, (c) defining a study population, (d) selecting endpoints, (e) defining interventional and controls arms, (f) blinding, (g) powering the study, and (h) duration of follow-up. In each case, we considered the strengths and weaknesses of different approaches in terms of scientific validity, ethical acceptability, practicality, and likelihood of bias. Results: We agreed that unlike evaluating therapies, attempting to judge the value of a diagnostic test based on eventual treatment success is conceptually flawed. Nonetheless, we explored the design of a hypothetical randomized controlled trial for this purpose, agreeing that: (1) the study population must sufficiently reflect its real-world counterpart; (2) clinical endpoints should include not only continence status but also other lower urinary tract symptoms and risks of management; (3) participants in the interventional arm should receive individualized management based on their UDS findings; (4) the most scientifically valid approach to the control arm—empiric treatment—is ethically problematic; (5) sufficient statistical power is imperative; and (6) ≥ 2 years\" follow-up is needed to assess the long-term impact of management. Conclusions: Although a perfect protocol does not exist, we recommend careful consideration of our observations when reflecting on past studies or planning new prospective research.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Nöroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Neurology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; CLINICAL NEUROLOGY; Nöroloji (klinik); Üroloji; Neurology (clinical); Urology; female urinary incontinence; prospective research; urodynamics; female urinary incontinence; prospective research; urodynamics